2018
DOI: 10.1002/bmc.4172
|View full text |Cite
|
Sign up to set email alerts
|

The issue of HPLC determination of endogenous lipoic acid in human plasma

Abstract: Lipoic acid (LA) is used extensively as a therapeutic agent for the treatment of various diseases. Many methods have been reported for the determination of LA plasma levels and its metabolites after its supplementation, but available information concerning endogenous plasma levels is still scarce. Studies which directly focused on determining the endogenous plasma levels provided highly controversial results, <4.9 nmol/L or 143.7-197.0 nmol/L. The main aim of this study was to verify the levels of free LA in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…HPLC-CD has been successfully applied to isoflavonoids and lignans [87], a wide range of other phenolic [88][89][90][91][92][93][94][95][96][97][98], lipophilic [89,99,100] and S-containing AOs [101][102][103][104][105] (Table 4). The limits of detection achieved are impressive (up to the fmol level).…”
Section: Coulometric Detection Of Antioxidants In Chromatography and Flow Systemsmentioning
confidence: 99%
“…HPLC-CD has been successfully applied to isoflavonoids and lignans [87], a wide range of other phenolic [88][89][90][91][92][93][94][95][96][97][98], lipophilic [89,99,100] and S-containing AOs [101][102][103][104][105] (Table 4). The limits of detection achieved are impressive (up to the fmol level).…”
Section: Coulometric Detection Of Antioxidants In Chromatography and Flow Systemsmentioning
confidence: 99%
“…Sechovcová et al (49) have reported that endogenous plasma levels of lipoic acid range between <4.9 and 197.0 nmol/l, determined using a conventional method. The authors developed a new method using high-performance liquid chromatography to determine endogenous lipoic acid levels.…”
Section: Discussionmentioning
confidence: 99%
“… Typical chromatograms with electrochemical detection of sulfur-containing antioxidants: ( a ) Chromatograms of plasma without addition of lipoic acid ( 1 ) and with additions of 1 ( 2 ), 5 ( 3 ), 7.5 ( 4 ), 15 ( 5 ) and 50 nM ( 6 ) of lipoic acid. Reprinted from [ 169 ], copyright 2017, with permission from John Wiley & Sons, Ltd. ( b ) Schematic illustration of the simultaneous determination of cysteine (Cys), homocysteine (hCys), glutathione (GSH), and methionine (Met) using green-synthesized Au nanoparticles/Au SPE. Reprinted from [ 177 ], copyright 2019, with permission from Elsevier.…”
Section: Figures Schemes and Tablesmentioning
confidence: 99%